2013
DOI: 10.2341/12-035-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Silorane-based Resin Composite for Restoring Conservative Cavities on the Changes in Cuspal Deflection

Abstract: After five minutes of curing, the change in the organic matrix of the resin composite using silorane has a positive effect on controlling the cumulative cuspal deflection. SUMMARYObjective: To investigate the effect of using two resin-composite materials for restoring conservative mesio-occluso-distal (MOD) cavities on the changes (incremental and cumulative) in cuspal deflection.Methods: Forty extracted sound human maxillary second premolars were subjected to standardized MOD cavity preparation and then divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…reported that silorane-based composite materials exhibited less polymerization shrinkage, resulting in reduced cuspal deflection. 11 New materials that have been recently marketed are called bulk-fill resin composite materials. The manufacturers claim that these materials produce less polymerization shrinkage when compared with traditional composites, 12 consequently reducing the cuspal deflection.…”
Section: Introductionmentioning
confidence: 99%
“…reported that silorane-based composite materials exhibited less polymerization shrinkage, resulting in reduced cuspal deflection. 11 New materials that have been recently marketed are called bulk-fill resin composite materials. The manufacturers claim that these materials produce less polymerization shrinkage when compared with traditional composites, 12 consequently reducing the cuspal deflection.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Marginal adaptation, which depends on poly merization shrinkage and resulting stress, should be assessed at baseline because both shrinkage and resulting stress take place during the placement of the restoration. 18 Other clinical factors, such as wear and the integrity of the adhesive interface, may have induced changes in marginal adaptation over 18 months. Siloranes are inherently hydrophobic and are a combination of siloxane and oxirane chemical moieties on each monomeric unit, where the siloxane provides a hydrophobic and chemically stable backbone, and the oxirane provides reactive groups that allow polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…This composite resin can only be used by its own self-etch adhesive system. 3 Silorane is obtained from the reaction of oxirane and siloxane molecules. SBC exhibits low polymerization shrinkage due to the ring-opening oxirane monomer and increases hydrophobicity due to the presence of siloxane species.…”
Section: Introductionmentioning
confidence: 99%
“…SBC exhibits low polymerization shrinkage due to the ring-opening oxirane monomer and increases hydrophobicity due to the presence of siloxane species. 3 …”
Section: Introductionmentioning
confidence: 99%